ASDAS, a highly discriminatory ASAS-endorsed disease activity score in patients with ankylosing spondylitis. Issue 12 (5th December 2008) - van der Heijde, D; Lie, E; Kvien, T K; Sieper, J; Van den Bosch, F; Listing, J; Braun, J; Landewé, R; ,
Abstract : Objectives: To evaluate various validity aspects of four disease activity scores (ASDAS) for ankylosing spondylitis (AS) in comparison with the Bath Ankylosing Spondylitis Disease Activity Index (BASDAI), its individual components and physician and patient global assessment of disease activity. Methods: The analyses were performed in two cohorts of patients with AS: (1) the NOR-DMARD database which includes patients starting on a disease-modifying antirheumatic drug or tumour necrosis factor (TNF) blocker and (2) patients participating in double-blind placebo controlled randomised clinical trials with TNF blockers in four centres. Discrimination between patients with low versus high disease activity according to various definitions and between various levels of change were analysed as the standardised mean difference (difference in the group means divided by the pooled SD of the group means) and t score. Results: The four ASDAS versions were highly discriminatory in differentiating patients with different levels of disease activity and patients with different levels of change. The ASDAS scores outperformed the BASDAI and its single components in all settings: patient- or physician-based, reflecting status or change, with normal or raised C-reactive protein (CRP), in the presence or absence of peripheral arthritis. There were no major differences between the four ASDAS scores. Based on feasibility, the ASAS membership selected the ASDAS version which included back pain, duration of morning stiffness, patient global assessment, peripheral joint complaints and CRP as the preferred version. Conclusions: The ASDAS is a validated, highly discriminatory instrument for assessing disease activity in AS, including patient-reported outcomes and CRP levels.